Human Antimicrobial Peptide Isolated From Triatoma infestans Haemolymph, Trypanosoma cruzi-Transmitting Vector - Diniz, Laura Cristina Lima; Miranda, Antonio; da Silva Jr., Pedro Ismael (Frontiers in Cellular and Infection Microbiology, 2018)
Antimicrobial peptides represent an interesting alternative to avoid commercial antibiotics resistance, due to physical and chemical. Blood sucking barber bug Triatoma infestans attracts social, economic and medical interest due its role in the transmission of Chagas' disease. Despite new researches, descriptions of AMPs from this insect remained elusive. Human FibrinopeptideA (FbPA) was isolated from T. infestans haemolymph through liquid chromatography, identified by mass spectrometry. This peptide presented antimicrobial activity against Micrococcus luteus. Native FbPA from human blood and synthetic FbPA also presented antimicrobial activity. The synthetic FbPA was conjugated with FITC and offered to the insects. After 72 hours, its hemolymph was collected and presented fluorescence on the same wavelength as FITC. Our experiments show that beyond intrinsic AMP production, T. infestans is able to co-opt molecules via internalization and may use them as antimicrobial peptides for protection.